Subjective Life Expectancy and Private Pensions - Tabea Bucher-Koenen; Sebastian Kluth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
One important parameter in the decision process when buying a private annuity is individuals' subjective life expectancy, because it directly infuences the expected rate of return. We examine the market for private annuities in Germany and evaluate potential selection e ects based on subjective life expectancy. First individuals are pessimistic about their life span compared to the o cial life tables. Second we nd a signi cant selection e ect based on subjective life expectancy for women invested in private annuity contracts|so-called Riester pensions. For men there seems to be no di erence in subjective life expectancy by Riester ownership. Comparing the size of this selection e ect with the underlying mark ups in life expectancy that are charged by the insurance industry shows that the latter appears to be in line for women but too high for men. Our ndings have strong policy implications. On the one hand miss-perceptions about longevity risk might prevent individuals from providing su ciently for retirement, on the other hand mandated unisex tari s appear to prevent men from investing in Riester pensions.
Keywords: D12; D91; G11; 330